Fabrication and characterization of functional chitosan/MXene composite films decorated with lead zirconate titanate nanoparticles - Ulu, Oznur Dogan; Ulu, Ahmet; Birhanli, Emre; Pekdemir, Mustafa Ersin; Atalay, Selcuk; Gelir, Ali; Ates, Burhan (Elsevier Science Sa, 2025)
The current study is intended to enhance unique bioactive and eco-friendly composite films following a simple solvent-casting method by incorporating lead zirconate titanate nanoparticles (PZT NPs) with chitosan (CHS)/ MXene matrix. Different characterization techniques were used in the examination of the obtained composite films and the basic physicochemical properties, electrical properties, antioxidant and antibacterial activities of the composite films were determined. The swelling degree, water uptake, and water solubility of the CHS/ MXene/PZT composite films decreased with the incorporation of PZT NPs, whereas the thermal stability increased. When PZT NPs were added, the tensile strength and elongation at break of composite films reached 1.32 MPa and 29.32 %, respectively, which were obviously higher than that of CHS/MXene film. Meanwhile, composite film had moderate antioxidant properties, which, interestingly, decreased with increasing PZT NPs content. In contrast, the obtained composite films showed good antibacterial activity against E. coli (11.00-16.80 mm) and S. aureus (12.20-18.60 mm), which gradually increased with the amount of PZT NPs. Meanwhile, the order of antibacterial activity was found to be S. aureus > E. coli, showing the selectivity of composite films. These results will shed light on additive selection for functional composite films of several applications.
Keywords: Chitosan; MXene; Lead zirconate titanate nanoparticles; Composite film